2017
DOI: 10.1097/spv.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregnancy and Delivery on Cytokine Expression in a Mouse Model of Pelvic Organ Prolapse

Abstract: Objectives The aim of this study was to determine the effect of pregnancy and delivery mode on cytokine expression in the pelvic organs and serum of lysyl oxidase like-1 knockout (Loxl1 KO) mice, which develop pelvic organ prolapse (POP) after delivery. Methods Bladder, urethra, vagina, rectum and blood were harvested from female Loxl1 KO mice during pregnancy, after vaginal or cesarean delivery, and from sham cesarean and unmanipulated controls. Pelvic organs and blood were also harvested from pregnant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Additionally, unlinked cell culture experiments [53], the presence of both elongated and round macrophages positive for M1 and M2 markers in IpL indicates that, in this specific tissue remodeling microenvironment, a more complex macrophage polarization spectra may be necessary to guarantee tissue homeostasis. This balance between proinflammatory and anti-inflammatory mediators is crucial to develop a process that could be considered “orderly” inflammation necessary for the activation of the wound-healing response and for tissue homeostasis to be restored [62], which seem to be essential to proper remodeling of the IpL since mouse LOXL1 −/− pelvic floor disorders after parturition are associated with both increased proinflammatory cytokine production at the pelvic organs [63] and exacerbated interpubic tissue relaxation during labor [12].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, unlinked cell culture experiments [53], the presence of both elongated and round macrophages positive for M1 and M2 markers in IpL indicates that, in this specific tissue remodeling microenvironment, a more complex macrophage polarization spectra may be necessary to guarantee tissue homeostasis. This balance between proinflammatory and anti-inflammatory mediators is crucial to develop a process that could be considered “orderly” inflammation necessary for the activation of the wound-healing response and for tissue homeostasis to be restored [62], which seem to be essential to proper remodeling of the IpL since mouse LOXL1 −/− pelvic floor disorders after parturition are associated with both increased proinflammatory cytokine production at the pelvic organs [63] and exacerbated interpubic tissue relaxation during labor [12].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a separate study ( 37 ) showed that compared with the levels in WT mice, the total and unit cell amounts of elastin and unit cell amount produced by non-epithelial vaginal cells in LOXL1-deficient mice were significantly reduced, while the ratio of MMP-9/TIMP-1 was relatively high. A recent study by Couri et al ( 64 ) indicated that in contrast to WT mice, the mRNA levels of chemokine C-X-C motif ligand 12 and chemokine C-C motif ligand 7 (mediators of inflammatory response) were differentially upregulated in the tissues of virgin Loxl1-KO mice, and they were significantly upregulated in the vagina, urethra, bladder, and rectum of pregnant Loxl1-KO mice. However, in Loxl1-KO mice after vaginal childbirth, cytokines were expressed differently in terms of time, tissue, and concentration.…”
Section: Fbln5 and Loxl1mentioning
confidence: 99%
“…These endogenous signals trigger a fast macrophage response and interact with toll-like receptors (TLRs), leading to a sterile inflammation process to solve the adverse condition that initially led to DAMP release 31 33 . Interestingly, aberrant modifications in the mouse reproductive tract or pelvic floor EMC molecules seem to be intimately associated with increased pro-inflammatory cytokine production in pelvic organs 34 and lead to exacerbated interpubic tissue relaxation for labor 15 .…”
Section: Introductionmentioning
confidence: 99%